Thermally reversible crosslinked copolymers: Solution and bulk behavior. (19th May 2017) - Laquièvre, Aurélie; Barrau, Sophie; Fournier, David; Stoclet, Gregory; Woisel, Patrice; Lefebvre, Jean-Marc
Abstract: A series of reversibly crosslinked copolymers based on ethyl methacrylate (EMA) and furfuryl methacrylate (FMA) with well-defined crosslink density were synthesized by Atom Transfer Radical Polymerization (ATRP) followed by Diels-Alder reaction using 4, 4'-bismaleimidodiphenylmethane (BM) as the linker. The network structure of the crosslinked copolymers was investigated in solution and in the solid state by means of swelling measurements and differential scanning calorimetry. The reversibility of the Diels Alder reaction (rDA) has been assessed in both cases. Nevertheless the behavior in the condensed state appears more complex as compared to the solution case, presumably owing to lower molecular mobility and stronger steric hindrances in the latter case. Calorimetric and dynamic viscoelastic characterizations provide evidence of the impact of crosslink density on the glass transition temperature and on the rubbery state response. The mechanical behavior upon uniaxial cold-drawing of the materials was investigated. The elementary plastic deformation mechanisms involved were assessed by Scanning Electronic Microcopy (SEM) and in situ Ultra-Small Angle X-ray Scattering (USAXS) experiments. It has been qualitatively shown that, while the reference copolymer deforms by crazing, the increase in crosslink density results in a decrease in craze density. The present work provides preliminary ground for using a reversible network modification route to tune the solid-state elementary deformation behavior of polymers while preserving the thermoplastic character in the molten state, i.e. without significant impact on processing and recyclability. Graphical abstract: Highlights: Assessment of the reversibility of the Diels-Alder reaction in solution and in the solid-state. Evaluation of effective entanglement molecular weight (Meff ) from rheological experiments as a function of crosslink density. Crosslinking impacts the mechanical behavior by delaying and reducing craze formation under stretching.